29th Annual GP2A Medicinal Chemistry Conference - Jean-Jacques Helesbeux; Laura Carro; Florence O. McCarthy; Vânia M. Moreira; Francesca Giuntini; Niamh O'Boyle; Susan E. Matthews; Gülşah Bayraktar; Samuel Bertrand; Christophe Rochais; Pascal Marchand (MDPI AG, 2021)
The 29th Annual GP2A (Group for the Promotion of Pharmaceutical chemistry in Academia) Conference was a virtual event this year due to the COVID-19 pandemic and spanned three days from Wednesday 25 to Friday 27 August 2021. The meeting brought together an international delegation of researchers with interests in medicinal chemistry and interfacing disciplines. Abstracts of keynote lectures given by the 10 invited speakers, along with those of the 8 young researcher talks and the 50 flash presentation posters, are included in this report. Like previous editions, the conference was a real success, with high-level scientific discussions on cutting-edge advances in the fields of pharmaceutical chemistry.